The Nexus: Estimation of Water Consumption for Hydropower in Brazil - Theodoros Semertzidis (Journal of Sustainable Development of Energy, Water and Environment Systems, 2019)

(untitled)
Recent major droughts in Brazil have given rise to discussions about water availability and security in relation to energy production. The relationship of the two resources, the water-energy nexus, is recognised as being of importance in literature and metrics for its estimation and understanding are sought after. One important aspect in understanding the water-energy nexus of hydroelectricity is estimating its water consumption and also its water footprint. In order to do this, this study uses a modified Penman-Monteith method to estimate evaporation from Brazil’s reservoirs for the period 2010-2016 and subsequently calculates the water footprint of hydroelectricity reservoirs. The results show the evaporation variation in space and time in the reservoirs and the differences of water consumed per unit of energy in Brazil. The discussion provides insight as to how the results can be valuable for future management and planning purposes.